PERAN UPPKA BKKBN PROVINSI BENGKULU DALAM MENINGKATKAN USAHA MIKRO KAMPUNG KB KOTA BENGKULU PERSPEKTIF EKONOMI SYARIAH (Studi Kasus di Kelurahan Lempuing Kec. Ratu Agung Kota Bengkulu) - Julita, Resi; Oktasari, Orin; Capriyanti, Orisa; Setiawan, Dedy Eko (ITB AAS Indonesia Surakarta, 2024)
The purpose of this research is to find out 1) the role of UPPKA BKKBN Bengkulu Province in increasing the income of micro businesses in the KB village of Bengkulu City. 2) and to find out the implementation of UPPKA BKKBN Bengkulu Province in increasing the income of micro businesses in the KB village of Bengkulu City from the perspective of Islamic economics. The research method used in this research is qualitative research method, with the type of field research. Data collection techniques using observation, interviews, and documentation. While the data analysis technique used is data reduction, data presentation, and conclusions or verification. The results of this study are: 1) The role of UPPKA BKKBN Bengkulu Province in increasing the income of micro businesses in the KB village of Bengkulu City. The UPPKA programme has an important role in increasing the income of micro businesses in the KB Village of Bengkulu City, which plays a role in providing training and advocacy, mentoring and evaluation, developing cooperation, facilitating and fostering, supervision and monitoring, providing assistance in solving problems, evaluating and updating programmes, and setting benchmarks for the success of a program. 2) Implementation of UPPKA BKKBN Bengkulu Province in increasing the income of micro businesses in the KB village of Bengkulu City from the perspective of Islamic economics. The UPPKA programme is an empowerment programme that is allowed according to sharia economics. This is in line with the Islamic recommendation that humans must work and seek sustenance in a halal and good way in order and apply the principle of tawhid to get the pleasure and value of worship. The business carried out by the UPPKA Gadis Cemara Indah group is also in accordance with the principles of production in Islam and does not commit usury and gharar. Keywords: Sharia Economics, Revenue, and UPPKA